LEGITIMATION OF VIRTUE EDUCATION IN TEACHER TRAINING DISCOURSE DURING SOVIET LATVIA - González, Manuel J Fernández (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Soviet virtue education had a relevant place in the discourse of the founders of communism and in the Communist Party’s documents. Virtue education played a central role in the construction of the future Soviet society and the raising of the New Soviet Man, a conscious communist, productive worker and soldier. This paper addresses two research questions: how was character and virtue education conceptualized, legitimized and implemented in Soviet Latvia? What elements of the Soviet approach to character education facilitated the consolidation of totalitarianism in Latvia?This research is based on written academic sources published in Soviet Latvia about virtue education and intended to school teachers: two teaching manuals for teacher training (Jesipovs & Gončarovs, 1948; Iļjina, 1971), and three collections scientific papers written by the leading educational academics of the Soviet Latvia published by the Latvian State University in 1962, 1964 and 1967 within the series “Questions about Upbringing in the Soviet school”.The findings highlight the understanding of virtue education during this period, and how it was ideologically, socially and pedagogically legitimized in the academic discourse and pedagogical literature addressed to school teachers.